2021
DOI: 10.32598/jhnm.31.1.2027
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Psychosocial Factors between Mothers of Infants with and without Physical Abnormalities

Abstract: Introduction: Congenital anomalies are one of the most important causes of disability and mortality in childhood seen in developing and developed countries. Mothers with physically-abnormal newborns have unfavorable lifestyle compared to mothers with healthy infants. Objective: The aim of this study was to determine the difference between mothers of infants with and without physical abnormalities in terms of psychosocial factors. Materials and Methods: This is a case-control study with two study groups; the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The current result reported that the highest mother's needs for emotional support were 1.31±.464. This result in agreement with [24] they mentioned that, mothers of infants with birth defects are significantly different from each other in terms of psychosocial factors revealed the relationship between inadequate perceived social Concerning mothers' needs for participation in child care had higher mean score was 1.22 ± .416. In this context [25] , reported that, mothers' mean duration of care participation increased as infants' recovery progressed at (15.82 ± 8.76).…”
Section: Discussionsupporting
confidence: 90%
“…The current result reported that the highest mother's needs for emotional support were 1.31±.464. This result in agreement with [24] they mentioned that, mothers of infants with birth defects are significantly different from each other in terms of psychosocial factors revealed the relationship between inadequate perceived social Concerning mothers' needs for participation in child care had higher mean score was 1.22 ± .416. In this context [25] , reported that, mothers' mean duration of care participation increased as infants' recovery progressed at (15.82 ± 8.76).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, a recent study by Ranjbar et al in Iran showed that the prevalence of alcohol use during pregnancy was higher in mothers of children with physical abnormalities than in mothers with healthy children (12).…”
Section: Dear Editormentioning
confidence: 98%